2014
DOI: 10.1515/gps-2014-0004
|View full text |Cite
|
Sign up to set email alerts
|

From trash to resource: a green approach to noble-metals dissolution and recovery

Abstract: Abstract:A process based on the lixiviant properties of organic mixtures of dihalogen/S,S-ligands, N,N′-dimethylperhydrodiazepine-2,3-dithione (Me 2 dazdt) and tetraalkylthiuramdisulphide (Et 4 TDS) in the presence of diiodine, for gold recovery from the non-ferrous metal fraction of real shredded waste electric and electronic equipment (WEEE), is presented here. Selective dissolution of metals is achieved through a sequence of three steps where the oxidation of different kinds of metals is achieved by using: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
1
15
0
1
Order By: Relevance
“…Unfortunately, these methods require harsh reaction conditions or hazardous reagents, [5–7] or both, in addition they are also unselectively dissolving all metals simultaneously. Recently, a new approach based on organic solvents and reactive ligand systems has been introduced [8–25] . These methods are mainly based on S ‐donor ligands [8–13,17,18] such as dithioxamides, [10] tetraethylthiuram disulfides, [8–13] pyridinethiols, [17,18] and/or halides [19–24] .…”
Section: Figurementioning
confidence: 99%
“…Unfortunately, these methods require harsh reaction conditions or hazardous reagents, [5–7] or both, in addition they are also unselectively dissolving all metals simultaneously. Recently, a new approach based on organic solvents and reactive ligand systems has been introduced [8–25] . These methods are mainly based on S ‐donor ligands [8–13,17,18] such as dithioxamides, [10] tetraethylthiuram disulfides, [8–13] pyridinethiols, [17,18] and/or halides [19–24] .…”
Section: Figurementioning
confidence: 99%
“…The results ( Fig. S3 in ESI †) showed that the imidazolium cations were attacked by chlorine gas, because new peaks were observed in the 1 Table 1), no changes in the NMR spectra were observed after transformation of the chloride into the trichloride ILs. ESI-MS spectra in the positive ionisation mode showed that the mass-to-charge ratios are in agreement with the cationic species in trichloride ILs (see ESI †).…”
mentioning
confidence: 99%
“…The mixture of Et 4 TDS and I 2 was also applied for gold recovery from real Waste Electrical and Electronic Equipment (WEEE) materials. 60 …”
Section: Solutions Of Halogens In Polar Organic Solventsmentioning
confidence: 99%